PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAN KONSUMEN DI RESTAURANT SENJA EATERY - Yohanes Paulus Hanny Wadhi; Yulianus Berto; Ni Wayan Noviana Safitri; Reynaldo Angga Siagian (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2023)
This research is designed as a case study. This quantitative case study with the research unit is the Twilight Eatery Restaurant from April 2023 to June 2023. The obstacles faced in marketing the Senja Eatery Restaurant products include a lack of employees and minimal promotion, namely only relying on social media such as Instagram which also has various limitations. Promotional activities offline such as distributing brochures, availability of highly disciplined employees. The marketing strategy carried out by Senja Eatery Restaurant is to carry out a marketing mix related to product, price, place, promotion, people, process and physical evidence. Marketing opportunities for Senja Eatery Restaurant are through social media such as Instagram, Facebook, WA, Google, and Tiktok.